Tinjauan Literatur: Efektivitas Maserasi sebagai Metode Ekstraksi Fitokimia - Ningsih, Arista Wahyu; Jihan Fahiroh Nur Arifin; Retno Wulan Devitri; Rusdiana Tri Septiarini; Elvira Silvany Zahara; Vira Maulidya; Yasmine Eka Maulidya; Elly Eka Rahmawati; Zakkiya Sabila; Zahratul Humaidah; Ivan Charles S.Klau (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Extraction is a crucial stage in obtaining bioactive compounds from natural materials that have potential as medicinal, cosmetic, or nutraceutical ingredients. Among the various extraction methods available, maceration remains one of the most widely used techniques due to its simplicity, cost-effectiveness, and ability to maintain the stability of active compounds. The maceration process involves soaking powdered plant material in a suitable solvent at room temperature for a certain period, accompanied by periodic stirring to facilitate the diffusion of active compounds into the solvent. This method is particularly effective for extracting polar and semi-polar compounds such as flavonoids, phenolics, and essential oils that are sensitive to heat. The review shows that the effectiveness of maceration is influenced by several key factors, including the type and concentration of solvent, particle size of the material, duration of soaking, and stirring frequency. The use of ethanol with higher concentrations generally yields greater extract recovery and higher levels of active compounds. In addition, maceration is considered environmentally friendly because it requires no excessive heating and can employ safe, natural solvents. Therefore, despite the development of advanced extraction technologies, maceration remains a relevant, practical, and efficient method for phytochemical extraction, especially in laboratory research and small-scale herbal industries.